2017
DOI: 10.2460/javma.250.5.530
|View full text |Cite
|
Sign up to set email alerts
|

Continuous radiotelemetric monitoring of intragastric pH in a dog with peptic ulceration

Abstract: CASE DESCRIPTION A 6-year-old castrated male Boxer was evaluated for a 5-week history of frequent vomiting, melena, and signs of abdominal pain following accidental ingestion of 5 to ten 15-mg meloxicam tablets (approx ingested dose, 3.1 to 6.2 mg/kg [1.4 to 2.8 mg/lb]). CLINICAL FINDINGS Clinical signs persisted despite 3 weeks of treatment with sucralfate (41.8 mg/kg [19 mg/lb], PO, q 8 h) and omeprazole (0.8 mg/kg [0.36 mg/lb], PO, q 24 h). Results of a CBC and serum biochemical analysis were unremarkable. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Enterohepatic recycling of NSAIDs likely plays a role whereby high concentrations of NSAIDs in bile are secreted into the duodenum in close proximity to the major duodenal papilla. Some of the most serious intestinal lesions in dogs caused by NSAIDs occur in this region . Small intestinal injury may be caused by increased numbers of gram‐negative facultative anaerobic bacteria that flourish in the SI of patients treated with PPIs.…”
Section: Mechanism Of Action Biological Targets Efficacy Adverse Ementioning
confidence: 99%
See 1 more Smart Citation
“…Enterohepatic recycling of NSAIDs likely plays a role whereby high concentrations of NSAIDs in bile are secreted into the duodenum in close proximity to the major duodenal papilla. Some of the most serious intestinal lesions in dogs caused by NSAIDs occur in this region . Small intestinal injury may be caused by increased numbers of gram‐negative facultative anaerobic bacteria that flourish in the SI of patients treated with PPIs.…”
Section: Mechanism Of Action Biological Targets Efficacy Adverse Ementioning
confidence: 99%
“…The ability to accurately and noninvasively measure intragastric pH with catheter‐less radiotelemetric pH monitoring devices (Bravo pH monitoring system, Medtronic Inc., Minneapolis, MN) in recent years has advanced our understanding of the effects of acid suppressants and dosing protocols on intragastric pH in animals and humans . Unfortunately, critical assessment of acid suppressants in experimental models and dogs and cats with spontaneous disease is sparse, and most of the studies evaluating the efficacy of acid suppressants were performed in healthy animals.…”
Section: Introductionmentioning
confidence: 99%
“…In dogs and cats, PPIs, including omeprazole, have demonstrated efficacy in increasing gastric pH, prescribed for managing dyspepsia, peptic ulceration, and gastroesophageal reflux disease [1,9]. Short-term administration of PPIs is generally well-tolerated in dogs and cats, with minor adverse effects, primarily self-limiting diarrhea and intestinal dysbiosis [4,7,10].…”
Section: Introductionmentioning
confidence: 99%
“…Although the inflammatory response is necessary for keeping the body healthy, when the inflammatory response is too intense, it can cause a large number of tissue rejection reactions and a series of knock-on effects. At present, non-steroidal anti-inflammatory drugs (NSAIDs) and corticosteroids are widely used in the treatment of inflammatory diseases ( Lane et al, 2017 ). Research has revealed that NSAIDs have the advantage of fast onset of action and are more commonly used in clinical practice, but pharmacokinetic and pharmacodynamic tests have shown that these drugs have side effects such as gastrointestinal mucosal damage ( Saganuwan and Orinya, 2016 ).…”
Section: Introductionmentioning
confidence: 99%